The Inhibitory Effect of Curosurf® and Alveofact® on the Formation of Neutrophil Extracellular Traps - Schulz, Annabell; Pagerols Raluy, Laia; Kolman, Jan Philipp; Königs, Ingo; Trochimiuk, Magdalena; Appl, Birgit; Reinshagen, Konrad; Boettcher, Michael; Trah, Julian (Frontiers in Immunology, 2021)
Background Neutrophil extracellular traps (NETs) are a defense mechanism in which neutrophils cast a net-like structure in response to microbial infection. NETs consist of decondensed chromatin and about 30 enzymes and peptides. Some components, such as neutrophil elastase (NE) and myeloperoxidase (MPO), present antimicrobial but also cytotoxic properties, leading to tissue injury. Many inflammatory diseases are associated with NETs, and their final role has not been identified. Pulmonary surfactant is known to have immunoregulatory abilities that alter the function of adaptive and innate immune cells. The aim of this study was to investigate the hypothesis that natural surfactant preparations inhibit the formation of NETs. Methods: The effect of two natural surfactants (Alveofact®, Curosurf®) on spontaneous and phorbol-12-myristate-13-acetate–induced NET formation by neutrophils isolated by magnetic cell sorting from healthy individuals was examined. NETs were quantitatively detected by absorption and fluorometric-based assays for the NET-specific proteins (NE, MPO) and cell-free DNA. Immunofluorescence microscopy images were used for visualization. Results: Both surfactant preparations exerted a dose-dependent inhibitory effect on NET formation. Samples treated with higher concentrations and with 30 minutes pre-incubation prior to stimulation with phorbol-12-myristate-13-acetate had significantly lower levels of NET-specific proteins and cell-free DNA compared to untreated samples. Immunofluorescence microscopy confirmed these findings. Conclusions: The described dose-dependent modulation of NET formation ex vivo suggests an interaction between exogenous surfactant supplementation and neutrophil granulocytes. The immunoregulatory effects of surfactant preparations should be considered for further examination of inflammatory diseases.